LET VERBE ET SES GROUPES - Ergashova Farangiz Oybek kizi; Ro'ziyeva Nasiba (Journal of new century innovations, 2022)
Annotation: This article describes the three groups of French verbs in the present tense, and how the verbs in each group change when they are added.